2007
DOI: 10.1088/0031-9155/52/24/012
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of exudates for diabetic retinopathy screening

Abstract: Automated image analysis is being widely sought to reduce the workload required for grading images resulting from diabetic retinopathy screening programmes. The recognition of exudates in retinal images is an important goal for automated analysis since these are one of the indicators that the disease has progressed to a stage requiring referral to an ophthalmologist. Candidate exudates were detected using a multi-scale morphological process. Based on local properties, the likelihoods of a candidate being a mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 18 publications
(25 reference statements)
3
58
0
5
Order By: Relevance
“…For BHs and exudates, the non-specific filter was applied at multiple scales and the results combined. 52,54 Dark objects were detected for BHs and bright objects were detected for exudates. The second stage of lesion detection performed more detailed analysis of the candidate lesions, measuring such features as their area, contrast and, for the dark lesions, the likelihood of it lying on a vessel.…”
Section: Lesion Detection and Image Quality Assessmentmentioning
confidence: 99%
“…For BHs and exudates, the non-specific filter was applied at multiple scales and the results combined. 52,54 Dark objects were detected for BHs and bright objects were detected for exudates. The second stage of lesion detection performed more detailed analysis of the candidate lesions, measuring such features as their area, contrast and, for the dark lesions, the likelihood of it lying on a vessel.…”
Section: Lesion Detection and Image Quality Assessmentmentioning
confidence: 99%
“…Automated bright lesion detection has resulted in highly accurate classification and has been discussed recently by [9], [10], [11]. For automated red lesion detection similar high sensitivity and specificity has been reported.…”
Section: Introductionmentioning
confidence: 84%
“…While the results of our algorithm showed higher performance in comparison to the abovementioned value. 10 In a similar study by Fleming et al, 11 they reported the sensitivity of 95.0% and the specificity of 84.6% for their applied method including morphological segmentation and dynamic thresholding using maximum likelihood estimation. The sensitivity of our technique was relatively lower than their results while our specificity was considerably higher than their reported value.…”
Section: Introductionmentioning
confidence: 92%